PENILAIAN KETERAMPILAN PROYEK - Fikri (Cross-border, 2020)
Evaluation is one of important step that must be done to measure the success of an educational program. In the evaluation there are several assessment instruments that can be used as a measuring tool to find out how much success is achieved by students and educators. Evaluation activities can cover all elements of learning, both directly and indirectly. At the evaluation stage there is an assessment. Assessment is not only useful for students but also very useful for educators. In addition to measuring the ability of students, the assessment can also motivate students in learning and hone the creativity and innovation of educators so that they can improve and develop learning. As we know, in the current assessment there are four kinds of assessment, namely spiritual assessment, social assessment, knowledge assessment and skills assessment. The four kinds of assessments complement each other for the achievement of Complete skill in students. To achieve the goal of the national education curriculum, namely mastery of 21st century skills for students. Through these measurements and assessments, it is hoped that educational institutions can maximize the goals of the national education curriculum. In the skills assessment there are several types of skills assessment such as performance skills assessment, project skills assessment, portfolio skills assessment and product skills assessment. In this paper the author tries to discuss one of the skills assessments, namely project skills assessment. Hopefully it can add insight to the reader because this paper will discuss a complete project skills assessment with qualitative literature methods.